2018
DOI: 10.1159/000488466
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on Clinical Outcome Parameters, Complication Rate and Survival after Radical Cystectomy: Evidence from a Prospective European Multicentre Study

Abstract: Background/Aims/Objectives: To evaluate the influence of body mass index (BMI) on complications and oncological outcomes in patients undergoing radical cystectomy (RC). Methods: Clinical and histopathological parameters of patients have been prospectively collected within the “PROspective MulticEnTer RadIcal Cystectomy Series 2011”. BMI was categorized as normal weight (<25 kg/m2), overweight (≥25–29.9 kg/m2) and obesity (≥30 kg/m2). The association between BMI and clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…Similarly, other retrospective studies confirmed the prognostic value of higher BMI in patients with both BC or UTUC [23,24] while another series suggested that also lowest value of BMI was associated to worst oncological outcomes [25]. On the contrary, other retrospective studies failed to find an association between BMI and oncological outcomes after surgery [26,27] while other confirmed a prognostic role only after RC without significant association after RNU [28,29]. Due to the absence of external and perspective validation of the results observed in retrospective series, the role of BMI in oncological outcomes prediction after surgery still remains unclear.…”
Section: Obesity and Risk Of Urothelial Cancermentioning
confidence: 86%
“…Similarly, other retrospective studies confirmed the prognostic value of higher BMI in patients with both BC or UTUC [23,24] while another series suggested that also lowest value of BMI was associated to worst oncological outcomes [25]. On the contrary, other retrospective studies failed to find an association between BMI and oncological outcomes after surgery [26,27] while other confirmed a prognostic role only after RC without significant association after RNU [28,29]. Due to the absence of external and perspective validation of the results observed in retrospective series, the role of BMI in oncological outcomes prediction after surgery still remains unclear.…”
Section: Obesity and Risk Of Urothelial Cancermentioning
confidence: 86%
“…The morbidity and mortality are among the highest in oncological surgery [3][4][5][6][7]. Influential factors are the high level of invasiveness combined with patient-derived factors such as the elevated mean patient's age and greater comorbidity [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen studies have assessed the association between body mass index (BMI) and prognosis [7,24,25,30,34,39,59,[65][66][67][68][69][70][71][72][73][74][75]. One study assessed BMI at diagnosis, [24] 13 studies assessed BMI at time of treatment (e.g., transurethral resection of bladder tumor (TURBT), radical cystectomy), [25,30,34,39,59,[65][66][67][68][69][70][71][72] and three studies did not report timing of BMI measurement [73][74][75].…”
Section: Body Mass Indexmentioning
confidence: 99%